Epidemiology of Stevens-Johnson syndrome and toxic epidermal necrolysis in the United States and factors predictive of outcomeCapsule Summary - Paul Wasuwanich, BSc; Joshua M. So, BA; Teja S. Chakrala, MD; Jinghua Chen, MD, PhD; Kiran Motaparthi, MD (Elsevier, 2023)
Background: Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and SJS-TEN overlap syndrome are rare severe cutaneous adverse reactions associated with high mortality. Objectives: To estimate incidence and describe trends of SJS/TEN hospitalizations in the United States and to describe the clinical, demographic, and geographic characteristics of affected patients and risk factors for mortality. Methods: We utilized hospitalization data from the 2010 to 2020 National Inpatient Sample. SJS, SJS-TEN overlap syndrome, and TEN were identified by International Classification of Diseases, 9th Revision and International Classification of Diseases, 10th Revision codes and analyzed by logistic regression. Results: We identified 51,040 hospitalizations involving SJS/TEN. Amog those, 37,283 (73.0%) were for SJS only, 7818 (15.3%) were for SJS-TEN overlap syndrome, and 7160 (14.0%) were for TEN only. Overall, SJS/TEN hospitalization rates declined over time, 2010 to 2020 (P < .05). Mortality rates of the SJS group, SJS-TEN overlap syndrome group, and TEN group were 5.4%, 14.4%, and 15.3%, respectively. Increasing age, chronic kidney disease, pneumonia, sepsis, and malignant neoplasm were all significantly associated with increased odds of mortality (P < .05). Non-Hispanic White racial/ethnic identification was associated with decreased odds of mortality (P < .05). Limitations: Lack of standardization for diagnostic criteria. Conclusions: Risk factors identified in this study lay the groundwork for improvement in SJS/TEN mortality prediction scoring.